ERα expression in T lymphocytes is dispensable for estrogenic effects in bone. Issue 2 (August 2018) - Gustafsson, K L; Nilsson, K H; Farman, H H; Andersson, A; Lionikaite, V; Henning, P; Wu, J; Windahl, S H; Islander, U; Movérare-Skrtic, S; Sjögren, K; Carlsten, H; et al.
Abstract : Estrogen treatment has positive effects on the skeleton, and we have shown that estrogen receptor alpha (ERα) expression in cells of hematopoietic origin contributes to a normal estrogen treatment response in bone tissue. T lymphocytes are implicated in the estrogenic regulation of bone mass, but it is not known whether T lymphocytes are direct estrogen target cells. Therefore, the aim of this study was to determine the importance of ERα expression in T lymphocytes for the estrogenic regulation of the skeleton using female mice lacking ERα expression specifically in T lymphocytes (Lck-ERα −/− ) and ERα flox/flox littermate (control) mice. Deletion of ERα expression in T lymphocytes did not affect bone mineral density (BMD) in sham-operated Lck-ERα −/− compared to control mice, and ovariectomy (ovx) resulted in a similar decrease in BMD in control and Lck-ERα −/− mice compared to sham-operated mice. Furthermore, estrogen treatment of ovx Lck-ERα −/− led to an increased BMD that was indistinguishable from the increase seen after estrogen treatment of ovx control mice. Detailed analysis of both the appendicular (femur) and axial (vertebrae) skeleton showed that both trabecular and cortical bone parameters responded to a similar extent regardless of the presence of ERα in T lymphocytes. In conclusion, ERα expression in T lymphocytes is dispensable for normal estrogenic regulation of bone mass in female mice.